(untitled) (Western Journal of Medical and Biomedical Sciences, 2025)
Foreign body ingestion is a recognized but infrequent complication of schizophrenia, particularly in individuals with poor treatment adherence and a lack of social support. Severe outcomes such as abdominal perforation are rare and pose significant diagnostic and therapeutic challenges. We aim to present a case report of abdominal perforation induced by foreign bodies ingestion in a vagrant patient suffering from Schizophrenia. This case report describes a 40-year-old vagrant, an unemployed male who had been suffering from schizophrenia for about five years without treatment, presenting with abdominal perforation due to the ingestion of multiple foreign objects. A multidisciplinary approach involving emergency surgery and psychiatric stabilization was employed in his management. Exploratory laparotomy revealed multiple foreign bodies in the stomach, including four and six-inch nails, currency notes, padlock keys, and plastic items. Postoperative psychiatric management led to symptom control with a switch to long acting injectable antipsychotics to improve adherence. The patient showed significant clinical and behavioural improvement and had remained in remission six months after his discharge and has been regular on follow-up. This case underscores the importance of integrated medical and psychiatric care in managing schizophrenia-related emergencies. It also demonstrates the effectiveness of long-acting antipsychotics in reducing relapse in patients with poor insight and adherence.